Gestão da informação e tecnologias: diretrizes para projetos da interface de museus virtuais no âmbito da autenticidade - Larissa Fernandes Dutra (2018)
This studys objective is to analyze how users have perceived the matter of authenticity within virtual museums and, with that, to elaborate guidelines for interface projects regarding their authenticity and the authenticity of their information. Through the deductive method, when we work with the theory about authenticity, we analyze a virtual museum site model - the Era Virtual project - in an attempt to create authenticity assessment indicators within these. After the practical analysis, a pilot questionnaire was developed and applied in order to validate the indicators created and, if necessary, the elaboration of new ones. Next, the final sample of the research was defined and the final questionnaires were applied. At the end of the research, we analyze the results obtained and then we create the guidelines of authenticity to help the Virtual Museums designers. It is identified that authenticity is a dynamic concept that concerns both scientifically verifiable questions through the matter of a digital object, and non material questions that emerge from the relation between men and this object. In general, the sample believes that the virtual museum visited is authentic and the main reason corroborating the perception of authenticity within virtual museums is its informative value.